Family participation profiles in Spanish educational centers - Alonso Sánchez, José Alexis; Álamo Bolaños, Arminda; Rodríguez Chirino, Paula (Revista Complutense de Educación, 2025)
INTRODUCTION: The involvement of families in educational institutions is a fundamental factor for the development of minors, contributing numerous benefits to all members of the educational community (Martins et al., 2020; Saracostti, et al., 2019; Yulianti et al., 2022). This study examined the profiles of families participating in schools. METHOD: The validated questionnaire "Family Involvement in Educational Centers" (León & Fernández, 2017) was used. Answered by 1433 families of students in Early Childhood, Primary, and Secondary Education, it consists of 37 items organized into four dimensions: family-school relationship, pedagogical support, participation, and training needs. Both descriptive and inferential statistical analyses were conducted using the SPSS statistical package, version 21. RESULTS: The results suggest that there is room for improvement in perception regarding participation. The most important predictor variables for the identified profiles are educational stage, age, and the number of children. Three profiles were identified: Profile 1, mostly consisting of respondents aged between 36 and 45, with children in primary education and an average of 2 children; Profile 2, with ages between 36 and 45, children in early childhood, and an average of 1 child; and Profile 3 (the most numerous), mainly composed of ages between 46 and 55, children in secondary education, and an average of 2 children. DISCUSSION: Although, according to the results obtained in the four dimensions, Profile 1 would seemingly have the highest family participation, considering the standard deviation, Profile 2 shows greater consistency and less variability in the different dimensions. This study significantly contributes to the understanding of family participation dynamics in the school context. The identified profiles provide valuable information for designing more precise and personalized intervention strategies.
Keywords: mothers and fathers; collaboration; involvement; education; schools